Nag Hammadi texts and the Bible: a synopsis and index - Evans, Craig A. (New testament tools and studies, 1993)
This volume places in synoptic form parallel texts from Nag Hammadi and from the Bible. This will enable scholars of Coptic Gnosticism, as well as scholars concerned with early Christian biblical interpretation, to make the comparisons necessary to determine relationships and what dependence, if any, there may be between these two bodies of material. This volume should facilitate the discussion concerning the origin, antiquity, and relationship of Gnosticism to Christianity. The volume also contains an extensive bibliography of materials relevant to this topic. Finally, a Scripture index will make it possible for the reader to find quickly any desired passage.